Apex of Triceps Aponeurosis: A Reliable Landmark to Localize the Radial Nerve. Issue 3 (14th July 2022) - Arora, Sumit; Kashyap, Abhishek; Garg, Rahul; Wadhawan, Akhil; Maini, Lalit
Abstract : Background: The posterior approach to the humerus is an extensile approach, which provides excellent access to the distal aspect of the humerus. The approach is traditionally utilized for internal fixation of fractures of the distal third of the humerus, to perform sequestrectomy, and for radial nerve exploration. The radial nerve is susceptible to damage when utilizing this approach 1 -3 . Hence, accurate localization of the radial nerve is required to aid in identification during dissection and to minimize the risk of palsy. Various anatomical landmarks have been described in the literature that can help locate the radial nerve intraoperatively. Description: The patient is anesthetized and placed in the lateral decubitus position with the elbow of the operative limb hanging freely over a bolster. A posterior midline incision centered over the fracture is made on the posterior aspect of the arm. The superficial and deep fascia are incised. The triceps aponeurosis is formed by the convergence and fusion of the lateral and long heads of the triceps. The most proximal confluence can be termed the "apex of the triceps aponeurosis." The radial nerve can be isolated approximately 2.5 cm proximal to the apex by developing an intramuscular plane. The remainder of the intramuscular dissection for plate fixation can then be performed safely without risking injury to the radial nerve. Alternatives: Numerous studies have established the relationship of the radial nerve to a fixed osseous point such as the medial epicondyle, lateral epicondyle, and angle of the acromion 4 -9 . Additionally, the wide range of measurements of these anatomic relationships, as reported in various studies, makes it difficult for the operating surgeon to locate the radial nerve, especially in the setting of a fractured humeral shaft. For example, the reported distance of the radial nerve from the lateral epicondyle ranges from 6 to 16 cm and the distance from the angle of the acromion ranges from 10 to 19 cm. Even identification of the superficial branch of the radial nerve has been shown to help intraoperative localization of the radial nerve 10 . However, these studies have been conducted on cadavers with intact humeri, and their accuracy has not been demonstrated on the patients in the clinical milieu of trauma. Rationale: The described soft-tissue landmark, which lies approximately 2.5 cm proximal to the apex of the triceps aponeurosis, reliably locates the radial nerve intraoperatively 11 . It is based on the anatomical fact that the origins of the lateral head (oblique ridge corresponding to the lateral lip of the spiral groove) and long head (infraglenoid tubercle of the scapula) are well above fractures of the middle and distal thirds of the humerus. Hence, the relationship of the radial nerve to the soft point represented by the apex of the aponeurosis is not likely to be disturbed in the setting of fractures distal to it, in sharp contrast with previously described osseous landmarks. Expected Outcomes: Employing this anatomical understanding resulted in early localization of the radial nerve (within 6 ± 1.5 minutes of skin incision) and less blood loss (188 ± 13 mL) 11 . Patients are likely to retain their ability to perform active dorsiflexion of the wrist and fingers and have sensory preservation in the distribution of autonomous zone of the radial nerve after the procedure. Important Tips: The relationship of the radial nerve to the soft point represented by the apex of the aponeurosis is not likely to be disturbed in the setting of typical fractures distal to it; however, this may differ in cases of severely displaced or comminuted fractures, and the surgeon should be aware of this fact. The surgeon should remain careful to protect the vena comitans.